NUMERICAL STUDY OF DYNAMIC RESPONSE OF STEEL STRUCTURES DUE TO VERTICAL EARTHQUAKE LOAD WITH CONSIDERING AXIAL FORCE IN COLUMN THAT PROPAGATE AND BOUNCE - PERMATA YENI - NIM: 25015307, INDAH
Generally, earthquake resistant structure is designed with horizontal earthquake because its big energy, however the earthquake load is not only in horizontal but also in vertical direction. The vertical earthquake will become axial tension and axial compressive force at column due to earthquake load from foundation. Clasic analysis of earthquake resistant structure considering that velocity of its propagation is assumed to be infinite. But it is different in high rise buildings, where the movement of foundation does not occur simultaneously with the movement of the up structure, its mean that the wave of earthquake propagates with a certain velocity within a certain time from the foundation to the top of the building. Fast or slow velocity of earthquake energy propagation surely affect the response of building structures. This research was conducted to determine the effect of vertical earthquake load in building column by considering the propagation and bounce of earthquake force. Analysis was performed on steel buildings 5, 10, and 15 floors. The structure is modeled in the shape of a pole, where every 3.5 meters height there is a steel mass approximated by a tributary mass of area 6 x 6 m2. Furthermore, the column is designed based on the necessary dimensions that are in accordance with applicable regulations. The three structures are burdened by the Kobe vertical earthquake load, 1994 and the vertical Northridge earthquake load, 1995. In this study, there are three methods of analysis, namely classical analysis with seismic force velocity is considered infinite, analysis by considering the propagation of earthquake where the velocity of earthquake propagation is finite, and analysis by considering the propagation and bounce of earthquake force. Finally, a comparison of the vertical earthquake impact of steel buildings with reinforced concrete buildings by looking at the percentage decrease of column capacity ratio. Results of analysis show that mass displacement follows the pattern of ground motion due to big axial stiffness of column. Vertical propagation increases mass displacement and axial force of column, then increases again when considering the propagation and bounce of earthquake forces, this is indicated by the decrease of column capacity ratio. The smallest column capacity ratio value is on the first floor column so that this column is in the most insecure condition. The higher a high rise building, then the effect of vertical earthquake will worsen the condition of the column indicated by decreasing of column capacity ratio. The percentage decrease of steel column capacity ratio is smaller than the reinforced concrete column because the earthquake force velocity on the steel building is larger.